Design and Implementation of NTU Wearable Exoskeleton as an Enhancement and Assistive Device - K. H. Low; X. Liu; H. Yu (Applied Bionics and Biomechanics)
This article presents a wearable lower extremity exoskeleton (LEE) developed to enhance the ability of a human’s walking while carrying heavy loads. The ultimate goal of the current research work is to design and control a power assist system that integrates a human’s intellect for feedback and sensory purposes. The exoskeleton system in this work consists of an inner exoskeleton and an outer exoskeleton. The inner exoskeleton measures the movements of the wearer and provides these measurements to the outer exoskeleton, which supports the whole exoskeleton system to walk following the wearer. A special footpad, which is designed and attached to the outer exoskeleton, can measure the zero moment point (ZMP) of the human as well as that of the exoskeleton in time. Using the measured human ZMP as the reference, the exoskeleton’s ZMP is controlled by trunk compensation so that the exoskeleton can walk stably. A simulation platform has first been developed to examine the gait coordination through inner and outer exoskeletons. A commercially available software, xPC Target, together with other toolboxes from MATLAB, has then been used to provide a real-time operating system for controlling the exoskeleton. Real-time locomotion control of the exoskeleton is implemented in the developed environment. Finally, some experiments on different objects showed that the stable walking can be achieved in the real environment.